Mighty baobab - WRENmedia (Technical Centre for Agricultural and Rural Cooperation, 2008)
The baobab tree has been used by man as a source of food and other materials for tens of thousands of years. In some parts of Africa, such as northern Ghana, the leaves, seeds and fruit pulp are a vitamin rich supplement to diets, particularly during the hungry season. The roots are also valued for their medicinal properties and there is growing interest in baobab products in the European market. As such, baobab deserves attention, having potential for adding value, processing and exporting of products, thereby boosting local economies.